Evaluation of Aqueous extracts of Hyptis suaveolens, Curcuma longa and Ixora coccinea against 3rd instar larva of Culex quinquefasciatus - Agada, Jeremiah; Umar, Yahaya Abdullahi; Dikwa, Kadaram Bukar; Ajibade, Gabriel Adeboyega (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Mosquitos have been implicated to be vectors of many debilitating diseases that affect both humans and livestock. Out of over 3500 mosquito species that have been identified, Culex quinquefasciatus stands out because they are hardy and can survive in different environmental conditions compared to Aedes species and Anopheles species. Culex quinquefasciatus are carriers of different pathogens ranging from bacteria, fungi, protozoans and helminths. This research aims to assess the larvicidal potential of aqueous solvent extract of the leaves of Hyptis suaveolens, Curcuma longa and Ixora coccinea against 3rd instar larva of Culex quinquefasciatus. Adult Culex quinquefasciatus were collected blood fed, reared in an entomological cage. The resulting 3rd instar of F1 generation were assayed using serial concentrations of 10 % stock solutions of the leaves extracts while feeding ad libitum. The result obtained revealed that aqueous extracts of the three plants at different concentrations (10 mg/L, 20 mg/L, 30 mg/L, 40 mg/L and 50 mg/L) was found to cause varied mortality in C. quinquefasciatus third (3rd) instar larvae after exposure. Extract of Hyptis suaveolens recorded significantly higher mortality (27.33 ± 0.57) at 50 mg/L concentration than H. suaveolens (14.67 ± 0.57) and C. longa (14.33 ± 0.57) when larvae were exposed to the same concentration. Lethal dosage studies required to yield 50 % and 90 % mortality for larvae were found to be smaller (LD 50 = 27.9 mg/L and LD 90 = 49.4 mg/L) when Ixora coccinea was tested compared to that of others tested. Out of the leaves extracts tested, Ixora coccinea was observed to be the most potent laicide. By way of recommendation, other plants should be tested on different mosquito species in a bid to obtain more plants that can control the vector.